Citation Patterns in Economics and Beyond: Assessing the Peculiarities of Economics from Two Scientometric Perspectives - Jakob Kapeller; Matthias Aistleitner; Stefan Steinerberger (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2017)
In this paper we explore three claims concerning the disciplinary character of economics by means of citation analysis. The three claims under study are: (1) economics exhibits strong forms of intellectual stratification and, as a byproduct, a rather pronounced internal hierarchy, (2) economists strongly conform to institutional incentives and (3) modern mainstream economics is a highly self-referential intellectual project mostly inaccessible to disciplinary or paradigmatic outsiders. The validity of these claims is assessed by means of an interdisciplinary comparison of citation patterns aiming to identify the peculiar characteristics of economic discourse. In exposing and discussing these peculiarities of economics, we emphasize the availability of two competing scientometric perspectives for assessing and interpreting our findings.
Keywords: A10; A12; A14; 330; citation patterns; economics; interdisciplinary; scientometrics; sociology of economics